Crenças e experiências de professores no PIBID de Língua Inglesa: interação e ressignificação? - Araújo, Paula Serralha (2015)
There are diverse studies about beliefs in Applied Linguistics since 1970 or so (BARCELOS, 2004), especially beliefs about teaching and learning Foreign Languages. The research about beliefs and experiences of English language teachers, who take part in a program of teaching incentive (Pibid), and, therefore, are immersed in public schools for elementary education, is relevant, once the (ac)knowledgment of these beliefs related to their teaching and learning experiences allows these teachers to reflect about the aspects that involve their teaching practice and their role as teachers of English language. The present work aims to investigate the interaction of beliefs and experiences related to foreign language teaching and learning of teachers who are participants of Pibid, in the subproject of English Language at the Federal University of Uberlândia (UFU), in 2013. The objective is to identify the beliefs and experiences about teaching and learning that the pre-service teachers (PI), the coordinator teacher (PF) and the supervisor teachers (PS) of the program show and how their beliefs and experiences influence each other and can or cannot be redefined. This is a qualitative and interpretative master’s research, in which I analized one narrative of each PI, one interview of PF and another of each PS, and, also, two meetings – the first between the PF and the PIs, and the second between all the participants in the subproject. All the data was collected at the end of their participation in Pibid, approximately one year and six months later. Therefore, I raised some beliefs and experiences about English language teaching and learning present in the teachers’ discourse and analized excerpts in their speech that evidenced the interaction with other participants and its influence to the formation, confirmation, demystification and redefinition of their beliefs. The results of this analysis bring elements that may help the constant reflection of university teachers, teachers in practice and pre-service teachers about the aspects that involve the teaching experiences in public schools.